2002
DOI: 10.1093/humrep/17.6.1468
|View full text |Cite
|
Sign up to set email alerts
|

An unusual steroid-producing ovarian tumour: Case report

Abstract: The rapid onset of virilization in a post-menopausal woman is usually the result of androgen secretion from a tumour of adrenal or ovarian origin. Androgen secreting neoplasms of the ovary are rare and usually show autonomous secretion. Rarely, these may be driven by the high levels of gonadotrophins seen in the post-menopausal state. We describe the case of a 67-year-old woman with high serum testosterone and estradiol in association with the high gonadotrophin levels usually associated with the post-menopaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
4

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 15 publications
3
24
0
4
Order By: Relevance
“…Therefore, the cetrorelix suppression test seems to be preferable as a diagnostic tool because maximal hormone suppression can be observed within several days. Our observations confirm and extend the report of Stephens et al (14), who described a similar case and documented the 24 h hormonal response to cetrorelix. Considering gonadal steroid half-lives and the biological variability in LH responsiveness of ovarian tumors, a 24 h cetrorelix suppression test is too short to achieve maximal suppression of the relevant androgens.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, the cetrorelix suppression test seems to be preferable as a diagnostic tool because maximal hormone suppression can be observed within several days. Our observations confirm and extend the report of Stephens et al (14), who described a similar case and documented the 24 h hormonal response to cetrorelix. Considering gonadal steroid half-lives and the biological variability in LH responsiveness of ovarian tumors, a 24 h cetrorelix suppression test is too short to achieve maximal suppression of the relevant androgens.…”
Section: Discussionsupporting
confidence: 93%
“…During the last two decades, several authors have reported the role of selective ovarian and adrenal venous catheterization as investigation for hyperandrogenism [9,10,12,13]. A unilateral androgen gradient allows the localization of the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…Os tumores do ovário associados a hiperandrogenismo incluem os tumores de células de Leydig, luteomas do estroma e tumores de células produtoras de esteroides não específicos 3,7 . Como já referido, os tumores produtores de androgénios podem ter também origem nas glândulas suprarrenais, embora estes sejam ainda mais raros 5,6 .…”
Section: Comentáriounclassified